EFFECTIVENESS OF NURSE THERAPEUTIC COMMUNICATION IN ENHANCING PATIENT COOPERATION DURING TREATMENT - Astuti, Andriani Mei; Novianti, Naycilla Putri; Santos, Nuno Martins dos; Pinto, Osvalda Maria; Azhar, Bayu (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Weaknesses in applying therapeutic communication are still a problem for nurses. This affects the quality of nursing services that have an impact on patient satisfaction. The purpose of this study was to identify to evaluate the effectiveness of nurse therapeutic communication in enhancing patient cooperation during treatment. This research method was an analytical survey method that used a cross-sectional approach. A cross-sectional study was conducted among 127 inpatients at Slamet Riyadi Hospital, Surakarta, in March 2024. Data were collected using three instruments: demographic questionnaire, therapeutic communication questionnaire (13 items; Cronbach’s Alpha = 0.824), and patient cooperation questionnaire (20 items; Cronbach’s Alpha > 0.80). Data were analyzed using descriptive statistics and linear regression. The results from this research most respondents reported consistent therapeutic communication (54.3%) and high cooperation (52.8%). A significant positive correlation was found between therapeutic communication and patient cooperation (p < 0.001; r = 0.552) showing that communication explained 41.5% of cooperation variance. Nurse therapeutic communication significantly improves patient cooperation. Enhancing nurses’ communication skills—empathy, respect, and active listening—supports patient-centered care and better health outcomes.